Malaysian Undergraduates’ Beliefs and Motivation for Learning Japanese as a Foreign Language - Soubakeavathi, Rethinasamy; Rokiah, Bt Paee; Ramanair, Joseph (Abdullah Kuzu, 2021)
Learninga foreign language is not a unique phenomenon in today’s globalised world. A survey by Japan Foundation indicates that Japanese language is one of the most popular foreign languages with approximately 2.98 million students studying Japanese language in over 133 countries around the globe. Despite ranking at number 10 in Southeast Asia, studies on Japanese language learning with a focus on Malaysian learners is scarce. This study explored the beliefs and motivation of Malaysian undergraduates taking Japanese as a foreign language. The study involved 150 undergraduates who were studying Japanese as a third language at a Malaysian university. The study employed a survey design using questionnaire which consisted of four sections focusing on participants’ demographic information, beliefs about language skills, self-efficacy beliefs related to the language skills, and reasons for learning the Japanese language. The findings indicate that most of the students are of the belief that listening and speaking are more difficult to learn compared to reading and writing skills. Similarly, most of the students are not confident with their ability to speak in Japanese. As for reasons for choosing to learn Japanese language, although a mix of integrative and instrumentalreasons were mentioned, integrative motives seem to take priority among the students. The paper also discusses the pedagogical implications of the findings on the teaching and learning of Japanese as a foreign language at tertiary level.